Investigations of ultrasonic velocity and absorption in aqueous solutions of [ampersand]alpha;- and [ampersand]beta;-cyclodextrin with sodium alkyl sulfates. Part 1. [ampersand]alpha;-cyclodextrin systems - Balcerzak, A.; Płowiec, R.; Juszkiewicz, A. (Archives of Acoustics, 2001)
In this part, the velocity and absorption measurements of ultrasonic waves in aqueous solutions of [ampersand]alpha;-cyclodextrin containing different sodium alkyl sulfates are reported. One or two relaxation processes for these solutions have been established. Thermodynamic and kinetic parameters related to these processes have been calculated. In the second part, experimental results for [ampersand]beta;-cyclodextrin will be reported and compared with those presented here.